Pembuatan Bandul Pemberat Mata Pancing dengan Teknik Pengecoran Logam dari Bahan Timah Solder Menggunakan Cetakan Aluminium - Prayoga, M. Angga; Purba, Jon Lihardo; Syahputra, Dwi Fawzi; Hermanto, Tino (CV. IRA PUBLISHING, 2024)
Making fishing rod weight pendulums using a metal casting process, namely by pouring molten metal into a mold, to produce the final shape of the product according to what we want. The aim of metal casting activities is to produce fishing rod weight pendulums using permanent aluminum molds, and identify defects in the casting results. The method used is a simple method, the materials used are portable stoves, portable gas cans, can melting furnaces, solder tin, aluminum molds, wire. From this research, it was obtained that casting results had several defects at the end of the casting process, namely the defects that occurred were mold shift defects (deformation defects), and hole defects (porosity defects). Through carrying out research on metal casting activities using simple tools, it was concluded that the results obtained from the metal casting process using aluminum molds were not good because there were many defects in the castings.